Efficacy and safety of ustekinumab in Japanese patients with moderately to severely active Crohn's disease: a subpopulation analysis of phase 3 induction and maintenance studies - Toshifumi Hibi; Yuya Imai; Yoko Murata; Nobuko Matsushima; Richuan Zheng; Christopher Gasink (Intestinal Research, 2017)
Background/Aims: Efficacy and safety of ustekinumab were evaluated in a Japanese subpopulation with moderately to severely active Crohn's disease (CD) in UNITI-1, UNITI-2 and IM-UNITI studies and results were compared with the overall population.Methods: Overall, patients in UNITI-1 (Japan, n=56; failed response to tumor necrosis factor antagonist) and UNITI-2 (Japan, n=26; failed response to prior conventional therapy) were randomized to placebo or ustekinumab intravenous induction (130 mg or ~6 mg/kg) at week 0. Responders to ustekinumab induction therapy (Japan, n=21) were randomized to placebo or ustekinumab (90 mg, subcutaneous) maintenance (every 12 weeks [q12w] or 8 weeks [q8w]) in IM-UNITI. The primary endpoint was clinical response at week 6 for induction studies and clinical remission at week 44 for maintenance study.Results: Percentage of patients achieving clinical response at week 6 was greater in ustekinumab 130 mg and ~6 mg/kg groups than in the placebo group (UNITI-1: 36.8% and 31.6% vs. 27.8%, respectively, for Japanese; 34.3% and 33.7% vs. 21.5%, respectively, for overall; UNITI-2: 37.5% and 55.6% vs. 11.1%, respectively, for Japanese; 51.7% and 55.5% vs. 28.7%, respectively, for overall). Clinical remission rate at week 44 during maintenance was greater in the ustekinumab 90 mg SC q12w and q8w groups than in the placebo group (50.0% and 55.6% vs. 25.0%, respectively, for Japanese; 48.8% and 53.1% vs. 35.9%, respectively, for overall). Efficacy and safety results observed in the Japanese subpopulation were generally consistent with those in the overall population.Conclusions: Ustekinumab could be considered as a new therapeutic option for moderately to severely active CD in Japanese patients. Both ustekinumab induction and maintenance treatments were generally well tolerated (Clinical Trial Registration: NCT01369329, NCT01369342, NCT01369355).